Matrix Transpose

Matrix Transpose

T Theorem: AT = A; (AB)T = BT AT : Matrix Transpose Transpose of matrix A is denoted AT , and formed by setting each column in AT from corresponding row in A. 1 4 2 2 1 Let A = ; B = : 2 3 −1 −1 0 2 2 −1 3 1 2 Then AT = ; BT = 2 −1 : 4 3 4 5 1 0 1 / 50 Matrix Transpose Transpose of matrix A is denoted AT , and formed by setting each column in AT from corresponding row in A. 1 4 2 2 1 Let A = ; B = : 2 3 −1 −1 0 2 2 −1 3 1 2 Then AT = ; BT = 2 −1 : 4 3 4 5 1 0 T Theorem: AT = A; (AB)T = BT AT : 1 / 50 I d × (`1) − b × (`2) =) (a d − c b) x1 = d β1 − b β2: I a × (`2) − c × (`1) =) (a d − c b) x2 = a β2 − c β1: Assume a d − c b 6= 0. 1 d β − b β 1 d −b β x = 1 2 = 1 a d − c b a β2 − c β1 a d − c b −c a β2 1 d −b = b def= A−1 b: a d − c b −c a Determinant: det (A) = a d − c b. So A−1 exists () det (A) 6= 0. x2.2 Inverse of Matrix (I) a b x β 2 × 2 system of equations A x = b: 1 = 1 : c d x2 β2 In scalar form: a x1 + b x2 = β1; (`1) c x1 + d x2 = β2: (`2) 2 / 50 Assume a d − c b 6= 0. 1 d β − b β 1 d −b β x = 1 2 = 1 a d − c b a β2 − c β1 a d − c b −c a β2 1 d −b = b def= A−1 b: a d − c b −c a Determinant: det (A) = a d − c b. So A−1 exists () det (A) 6= 0. x2.2 Inverse of Matrix (I) a b x β 2 × 2 system of equations A x = b: 1 = 1 : c d x2 β2 In scalar form: a x1 + b x2 = β1; (`1) c x1 + d x2 = β2: (`2) I d × (`1) − b × (`2) =) (a d − c b) x1 = d β1 − b β2: I a × (`2) − c × (`1) =) (a d − c b) x2 = a β2 − c β1: 2 / 50 1 d −b = b def= A−1 b: a d − c b −c a Determinant: det (A) = a d − c b. So A−1 exists () det (A) 6= 0. x2.2 Inverse of Matrix (I) a b x β 2 × 2 system of equations A x = b: 1 = 1 : c d x2 β2 In scalar form: a x1 + b x2 = β1; (`1) c x1 + d x2 = β2: (`2) I d × (`1) − b × (`2) =) (a d − c b) x1 = d β1 − b β2: I a × (`2) − c × (`1) =) (a d − c b) x2 = a β2 − c β1: Assume a d − c b 6= 0. 1 d β − b β 1 d −b β x = 1 2 = 1 a d − c b a β2 − c β1 a d − c b −c a β2 2 / 50 Determinant: det (A) = a d − c b. So A−1 exists () det (A) 6= 0. x2.2 Inverse of Matrix (I) a b x β 2 × 2 system of equations A x = b: 1 = 1 : c d x2 β2 In scalar form: a x1 + b x2 = β1; (`1) c x1 + d x2 = β2: (`2) I d × (`1) − b × (`2) =) (a d − c b) x1 = d β1 − b β2: I a × (`2) − c × (`1) =) (a d − c b) x2 = a β2 − c β1: Assume a d − c b 6= 0. 1 d β − b β 1 d −b β x = 1 2 = 1 a d − c b a β2 − c β1 a d − c b −c a β2 1 d −b = b def= A−1 b: a d − c b −c a 2 / 50 x2.2 Inverse of Matrix (I) a b x β 2 × 2 system of equations A x = b: 1 = 1 : c d x2 β2 In scalar form: a x1 + b x2 = β1; (`1) c x1 + d x2 = β2: (`2) I d × (`1) − b × (`2) =) (a d − c b) x1 = d β1 − b β2: I a × (`2) − c × (`1) =) (a d − c b) x2 = a β2 − c β1: Assume a d − c b 6= 0. 1 d β − b β 1 d −b β x = 1 2 = 1 a d − c b a β2 − c β1 a d − c b −c a β2 1 d −b = b def= A−1 b: a d − c b −c a Determinant: det (A) = a d − c b. So A−1 exists () det (A) 6= 0. 2 / 50 Definition: Matrix A 2 Rn×n is invertible if there exists matrix 2 1 0 ··· 0 3 6 0 1 ··· 0 7 C 2 Rn×n so that CA = I = AC; with I = 6 7 identity. 6 . .. 7 4 . 5 0 0 ··· 1 C is called inverse of A, denoted as A−1. Inverse of Matrix (I) a b 1 d −b 2 × 2 matrix A = ; A−1 = : c d a d − c b −c a 1 0 Let I = be the identity matrix. Then 0 1 AI = IA = A; I x = x for all A and x. 1 d −b a b A−1 A = = I = AA−1: a d − c b −c a c d 3 / 50 Inverse of Matrix (I) a b 1 d −b 2 × 2 matrix A = ; A−1 = : c d a d − c b −c a 1 0 Let I = be the identity matrix. Then 0 1 AI = IA = A; I x = x for all A and x. 1 d −b a b A−1 A = = I = AA−1: a d − c b −c a c d Definition: Matrix A 2 Rn×n is invertible if there exists matrix 2 1 0 ··· 0 3 6 0 1 ··· 0 7 C 2 Rn×n so that CA = I = AC; with I = 6 7 identity. 6 . .. 7 4 . 5 0 0 ··· 1 C is called inverse of A, denoted as A−1. 3 / 50 2 0 1 2 3 2 −9 14 −3 3 1 EX: A = 1 0 3 ; then (later show) A−1 = −4 8 −2 : 4 5 2 4 5 4 −3 8 3 −4 1 2 1 3 2 1 3 2 −13 3 −1 A x = 4 −1 5 has solution x = A 4 −1 5 = 4 −7 5 : 1 1 4 Inverse of Matrix (II) 3 2 1 4 −2 EX: Let A = ; then A−1 = : 1 4 10 −1 3 3 2 1 1 1 8 x = has solution x = A−1 = : 1 4 −2 −2 10 −7 4 / 50 Inverse of Matrix (II) 3 2 1 4 −2 EX: Let A = ; then A−1 = : 1 4 10 −1 3 3 2 1 1 1 8 x = has solution x = A−1 = : 1 4 −2 −2 10 −7 2 0 1 2 3 2 −9 14 −3 3 1 EX: A = 1 0 3 ; then (later show) A−1 = −4 8 −2 : 4 5 2 4 5 4 −3 8 3 −4 1 2 1 3 2 1 3 2 −13 3 −1 A x = 4 −1 5 has solution x = A 4 −1 5 = 4 −7 5 : 1 1 4 4 / 50 T −1 −1T I A = A −1 −1 −1 I (AB) = B A Proof: B−1 A−1 (AB) = B−1 A−1 A B = B−1 B = I Similarly (AB) B−1 A−1 = I : Therefore (AB)−1 = B−1 A−1 . QED Inverse Matrix (III) Theorem: Let A; B 2 Rn×n be invertible −1−1 I A = A 5 / 50 −1 −1 −1 I (AB) = B A Proof: B−1 A−1 (AB) = B−1 A−1 A B = B−1 B = I Similarly (AB) B−1 A−1 = I : Therefore (AB)−1 = B−1 A−1 . QED Inverse Matrix (III) Theorem: Let A; B 2 Rn×n be invertible −1−1 I A = A T −1 −1T I A = A 5 / 50 Inverse Matrix (III) Theorem: Let A; B 2 Rn×n be invertible −1−1 I A = A T −1 −1T I A = A −1 −1 −1 I (AB) = B A Proof: B−1 A−1 (AB) = B−1 A−1 A B = B−1 B = I Similarly (AB) B−1 A−1 = I : Therefore (AB)−1 = B−1 A−1 . QED 5 / 50 interchange I E1;3 obtained by row1 () row3 on I . Elementary Operation =) Elementary Matrix (E1;3) 2 3 a11 a12 a13 Let A = 4 a21 a22 a23 5 a31 a32 a33 interchange I row1 () row3 2 3 2 3 2 3 a31 a32 a33 0 0 1 a11 a12 a13 A =) 4 a21 a22 a23 5 = 4 0 1 0 5 4 a21 a22 a23 5 a11 a12 a13 1 0 0 a31 a32 a33 def = E1;3 A 6 / 50 Elementary Operation =) Elementary Matrix (E1;3) 2 3 a11 a12 a13 Let A = 4 a21 a22 a23 5 a31 a32 a33 interchange I row1 () row3 2 3 2 3 2 3 a31 a32 a33 0 0 1 a11 a12 a13 A =) 4 a21 a22 a23 5 = 4 0 1 0 5 4 a21 a22 a23 5 a11 a12 a13 1 0 0 a31 a32 a33 def = E1;3 A interchange I E1;3 obtained by row1 () row3 on I . 6 / 50 I Eb2 obtained by row3 − 2 row1 =) row3 on I . Elementary Operation =) Elementary Matrix (Eb2) 2 3 a11 a12 a13 Let A = 4 a21 a22 a23 5 a31 a32 a33 I row3 − 2 row1 =) row3 2 3 a11 a12 a13 A =) 4 a21 a22 a23 5 a31 − 2 a11 a32 − 2 a12 a33 − 2 a13 2 3 2 3 1 0 0 a11 a12 a13 def = 4 0 1 0 5 4 a21 a22 a23 5 = Eb2 A −2 0 1 a31 a32 a33 7 / 50 Elementary Operation =) Elementary Matrix (Eb2) 2 3 a11 a12 a13 Let A = 4 a21 a22 a23 5 a31 a32 a33 I row3 − 2 row1 =) row3 2 3 a11 a12 a13 A =) 4 a21 a22 a23 5 a31 − 2 a11 a32 − 2 a12 a33 − 2 a13 2 3 2 3 1 0 0 a11 a12 a13 def = 4 0 1 0 5 4 a21 a22 a23 5 = Eb2 A −2 0 1 a31 a32 a33 I Eb2 obtained by row3 − 2 row1 =) row3 on I .

View Full Text

Details

  • File Type
    pdf
  • Upload Time
    -
  • Content Languages
    English
  • Upload User
    Anonymous/Not logged-in
  • File Pages
    100 Page
  • File Size
    -

Download

Channel Download Status
Express Download Enable

Copyright

We respect the copyrights and intellectual property rights of all users. All uploaded documents are either original works of the uploader or authorized works of the rightful owners.

  • Not to be reproduced or distributed without explicit permission.
  • Not used for commercial purposes outside of approved use cases.
  • Not used to infringe on the rights of the original creators.
  • If you believe any content infringes your copyright, please contact us immediately.

Support

For help with questions, suggestions, or problems, please contact us